Mechanical properties and surface roughness of polymer-based materials containing DCPD particles - Mateus Silva VILELA; Vitória Leão BERNAL; Laura Luciana César CHAGAS; Flávio Maron VICHI; Ana Cecília Corrêa ARANHA; Victor Elias ARANA-CHAVEZ; Roberto Ruggiero BRAGA; Marcela Charantola RODRIGUES (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The purpose of this study was to synthesize dicalcium phosphate dihydrate (DCPD) particles functionalized with triethylene glycol dimethacrylate (TEGDMA) through different routes by varying the receptor solution: ammonium phosphate (AP groups) or calcium nitrate (CN groups) and the moment in which TEGDMA was incorporated: ab initio (ab) or at the end of dripping the solution (ap). Two syntheses were performed without adding TEGDMA (nf). The particles were characterized by X-ray diffractometry, true density (using a helium pycnometer), surface area, and scanning electron microscopy. A 20 vol% of DCPD particles from the D, E, and F groups was added to the resin matrix to determine the degree of conversion (DC), biaxial flexural strength (BFS), the flexural modulus (FM), and surface roughness after an abrasive challenge (RA). A group with silanized barium glass particles was tested as a control. The data were submitted to ANOVA/Tukey's test (DC, BFS, and RA), and the Kruskal-Wallis test (FM) (alpha = 0.05). BFS values varied between 83 and 142 MPa, and the CN_ab group presented a similar value (123 MPa) to the control group. FM values varied between 3.6 and 8.7 GPa (CN_ab and CN_nf groups, respectively), with a significant difference found only between these groups. RA did not result in significant differences. The use of calcium nitrate solution as a receptor, together with ab initio functionalization formed particles with larger surface areas. Higher BFS values were observed for the material containing DCPD particles with a higher surface area. In general, the DC, FM, and RA values were not affected by the variables studied.